Body Adiposity, But Not Elements of Objectively Measured Sedentary Behavior or Physical Activity, Is Associated With Circulating Liver Enzymes in Adults With Overweight and Obesity - Laine, Saara; Sjöros, Tanja; Vähä-Ypyä, Henri; Garthwaite, Taru; Löyttyniemi, Eliisa; Sievänen, Harri; Vasankari, Tommi; Knuuti, Juhani; Heinonen, Ilkka H. A. (Frontiers in Endocrinology, 2021)
Objective We studied the associations between accelerometer-measured sedentary behavior (SB) and habitual physical activity (PA) as well as markers of body adiposity and other cardiometabolic risk factors with liver enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST) and γ-glutamyltransferase (GGT). Methods A total of 144 middle-aged adults (mean age 57 (SD 6.5) years) with overweight or obesity (mean body mass index [BMI] 31.8 [SD 3.9] kg/m2) participated. Different components of SB (sitting, lying) and PA (standing, breaks in SB, daily steps, light PA, moderate-to-vigorous PA and total PA) were measured with validated hip-worn accelerometers for four consecutive weeks (mean 25 days, [SD 4]). Fasting venous blood samples were analysed using standard assays. The associations were examined with Pearson’s partial correlation coefficient test and linear mixed model. Results Among 102 women and 42 men accelerometer measured SB or the elements of PA were not associated with circulating liver enzymes. When adjusted for age and sex, liver enzymes correlated positively with BMI and waist circumference (WC) (ALT r=0.34, p<0.0001, r=0.41, < 0.0001, AST r=0.17, p=0.049, r=0.26, p=0.002, GGT r=0.29, p=0.0005, r0.32, p < 0.0001, respectively). SB proportion associated positively with BMI (r=0.21, p=0.008) and WC (r=0.27, p=0.001). Components of PA associated negatively with BMI (MVPA r=-0.23, p=0.005, daily steps r=-0.30, p<0.0001 and breaks in sedentary time r=-0.32, p<0.0001), as well as with WC (breaks in SB r=-0.35, p<0.0001, MVPA r=-0.26, p=0.002, daily steps r=-0.31, p<0.0001, standing time r=-0.27, p=0.001). Liver enzymes associated positively with common cardiometabolic markers such as resting heart rate (ALT; β=0.17, p=0.03, AST; β=0.25, p=0.002, GGT; β=0.23, p=0.004) and systolic / diastolic blood pressure (ALT β=0.20, p=0.01, β=0.22, p=0.005, AST (only diastolic) β=0.23, p=0.006, GGT β=0.19, p=0.02, = 0.23, p=0.004, respectively), fasting insulin (ALT β=0.41, p<0.0001, AST β=0.36, p=0.0003, GGT β=0.20, p=0.04) and insulin resistance index (ALT β=0.42, p<0.0001, AST β=0.36, p=0.0003, GGT β=0.21, p=0.03), even after adjustment with BMI. Conclusions Liver enzymes correlate with body adiposity and appear to cluster with other common cardiometabolic risk factors, even independently of body adiposity. SB and PA appear not to be essential in modulating the levels of circulating liver enzymes.